Culture Influence to Students' Interaction due to Achieving Deep Learning Process in Problem Based Learning - Hikmawati Nurokhmanti; Herma Roebertsens (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: In order achieving deep learning in tutorial process, collaboration among member of tutorial group becomes important factor. The quality of collaboration is determined by the students’ interaction which is influenced by students’ perception sourced from culture. This study aimed to reveal the relationship between students’ cultural perception with their interaction in tutorial.Method: This study used quantitative approach with distributing questionnaire to students in lecturer session during June – July 2012. The Pleijers et al questionnaire was used in this study. While question for cultural perception were extracted from theoretical background: teacher dependencies, group influence, learning orientation, ethnic influence, and response to feedback. Pearson or Spearman correlation test was chosen for further analysis.Results: There is correlation between students’ interaction with their perspectives since each type of interaction had significant r-value with specific students’ perspectives. Explorative and cumulative reasoning type of interaction could be endangered by students who have negative learning orientation, easily influenced by inactive group, and negative response to feedback. While handling conflict type of interaction is influenced by students’ perception on their ethnicity and response to feedback.Conclusion: Expected interaction during tutorial is complex situation which is influenced by students’ perspectives. Thus also involve teacher as tutor who also has perspectives derived from culture. Another research on tutor derived culture perspectives should be further explored.